2020
DOI: 10.1002/cbin.11310
|View full text |Cite
|
Sign up to set email alerts
|

AMPK activation suppresses mTOR/S6K1 phosphorylation and induces leucine resistance in rats with sepsis

Abstract: Although it has been known that protein synthesis is suppressed in sepsis, which cannot be corrected by leucine supplement (also known as leucine resistance), the molecular signaling mechanism remains unclear. This study aimed to investigate the AMP-activated protein kinase/mammalian target of rapamycin (AMPK/mTOR) pathway in sepsis-induced leucine resistance and its upstream signals, and to seek a way to correct leucine resistance in sepsis. Sepsis was produced by cecal ligation and puncture (CLP) model in ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…These results indicated that the inhibition of MAGE‐A6 enhanced the radiosensitivity of non‐small cell lung cancer cells. On the other hand, the activation of AMPK inhibited the expression of p‐S6K1 31 . Upregulation of p‐S6K1 promoted the development of colorectal cancer 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated that the inhibition of MAGE‐A6 enhanced the radiosensitivity of non‐small cell lung cancer cells. On the other hand, the activation of AMPK inhibited the expression of p‐S6K1 31 . Upregulation of p‐S6K1 promoted the development of colorectal cancer 32 .…”
Section: Discussionmentioning
confidence: 99%
“…*p <.05, **p <.01, and ***p <.001cell lung cancer cells. On the other hand, the activation of AMPK inhibited the expression of p-S6K1 31. Upregulation of p-S6K1 promoted the development of colorectal cancer 32.…”
mentioning
confidence: 99%
“…In contrast, AMPK activates mTORC2 to enhance cell survival under nutrient stress [ 215 ]. AMPK dephosphorylates to inactivate mTOR and its downstream S6K1 and 4EBP1 [ 216 ]. AMPK is validated as upstream of SREBP.…”
Section: Akt Effectors Modulate Cell Functionsmentioning
confidence: 99%
“…This indicated that the effects of leucine might be different in different patients and this should be considered to better individualize nutrition to the critically ill. The second issue is that in animal models of sepsis there is a leucine resistance which is due to a high phosphorylation of AMPK which inhibits the activation of mTOR by leucine [12 ▪ ]. Whether this leucine resistance also exists in critically ill patient and if it possibly can be overcome by higher leucine dosage or HMB has not been investigated.…”
Section: Mechanism Of Actionmentioning
confidence: 99%